Protocolo para sinterização de zircônia odontológica por energia de micro-ondas - Barchetta, Nayara Fernanda [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study aimed to evaluate the impact of sintering and cooling temperatures in the mechanical and microstructural behavior of microwave-sintered Y-TZP ceramics. The sintering and cooling temperatures were varied at given range in order to develop a protocol, which could maintain the zirconia microstructure compatible to the one obtained by conventional sintering. Thus, in this study the sintering process was optimized with the use of the main microwave energy qualities: energy-saving, reduced processing time and volumetric energy absorption by the material. Eighty-four discs were prepared with CAD-CAM (n=84) for discs size standardization, following ISO 6872. The discs were distributed into 7 groups (n=12), Control Group = conventional sintering. Other Groups, with microwave-sintered discs, with variations in sintering (S) and cooling (R) temperatures, formed the following sub-groups: S1400RR, S1400R400, S1400R25, S1450RR, S1450R400 and S1450R25. For microstructural analysis, the following characterizations were performed: Density, XRD and SEM; mechanical analysis was performed via biaxial flexure resistance. The flexure resistance data were statistically analyzed (two-way ANOVA, Tukey, Sidak and Dunnett). The Control (806,1±105,8 MPa) and S1450 (824,7±99,12 MPa) Groups did not present differences; only discs from Groups sintered at 1400ºC (681,9±91,17 MPa) showed lower averages. The same occurred when density values were analyzed. From XRD analysis, it was observed that all groups had remained in the tetragonal phase for a larger period. In conclusion, it can be proposed a protocol for microwave sintering: temperature 1450 ° C for 15 min and fast cooling. The method of microwave sintering presents compatibility with the conventional method and allows process optimization

Este trabalho teve como objetivo avaliar o impacto da temperatura de sinterização e resfriamento, no comportamento mecânico e microestrutural da cerâmica odontológica Y-TZP, sinterizada por energia de micro-ondas. Variaram-se a temperatura de sinterização e resfriamento a fim de se desenvolver um protocolo, que mantenha a microestrutura da zircônia compatível à obtida com sinterização convencional. Dessa forma, buscou-se otimizar o processo fazendo uso das principais vantagens da energia de micro-ondas: economia de energia, tempo de processo reduzido e absorção volumétrica de energia pelo material. Foram confeccionados N=84 discos por meio de CAD-CAM para obter padronização no tamanho dos discos de acordo com a ISO 6872, os discos foram divididos em 7 grupos n=12, o Grupo Controle foi sinterizado de modo convencional, e os Grupos Experimentais foram sinterizados por energia de micro-ondas, nos quais variaram-se a temperatura de sinterização (S) e a temperatura de resfriamento (R), formando os grupos: S1400RR, S1400R400, S1400R25, S1450RR, S1450R400 e S1450R25. Para caracterização microestrutural foram realizadas medidas de densidade, análises de difração de raios-X (DRX), microscopia eletrônica de varredura (MEV) e tamanho de grãos. A caracterização mecânica foi realizada por meio de ensaios de resistência à flexão biaxial. Os resultados de resistência à flexão obtidos foram analisados estatisticamente (ANOVA, Tukey, Sidak e Dunnett), sendo que os Grupos Controle (806,1±105,8 MPa) e S1450 (824,7±99,12 MPa) não se diferenciaram. Somente os Grupos sinterizados à 1400 °C (681,9±91,17 MPa) apresentaram médias inferiores. Este mesmo fato ocorreu quando se analisou a densidade. A análise de DRX mostrou que a fase tetragonal prevaleceu em todos os grupos. Pode-se então, sugerir um protocolo ideal para sinterização de Y-TZP por energia de micro-ondas:...
Keywords: Cerâmica; Microondas; Materiais dentários; Dental materials